Building Resilience: Climate Risk Mapping and Adaptation Planning in 10 barangays in Guinayangan, Quezon - Gutierrez, Mary Anne; Raviz, Jeny; Garcia, Cornelia A. (International Rice Research Institute, 2024)
The Municipality of Guinayangan, a third-class and rapidly developing area in Quezon Province, relies heavily on coconut and rice production, which contributes signifiacatly to its local economy. Despite ongoing development, agricultural production in Guinayangan remains highly vulnerable to climate-related threats, including typhoons, El Niño, and La Niña events. To address these challenges, the CGIAR Research Initiative on Climate Resilience (ClimBeR), in partnership with the International Institute of Rural Reconstruction (IIRR) and the local government, has implemented the Climate-Smart Mapping and Adaptation Planning (CS-MAP) across 10 barangays in Guinayangan. CS-MAP, a participatory mapping approach developed by CCAFS-SEA, aims to assess climate risks, identify vulnerable areas, and propose location-specific adaptation strategies.